Building models of Neanderthal territories from raw material transports in the Aquitaine Basin (southwestern France). (17th March 2017) - Turq, Alain; Faivre, Jean-Philippe; Gravina, Brad; Bourguignon, Laurence
Abstract: The Middle Palaeolithic of southwestern France has long been a testing ground for models of Neanderthal lithic assemblage variability and mobility strategies. Advances in our understanding of the lithological structure of the northern Aquitaine Basin combined with numerous raw material studies allows connections between different areas of the region to be revealed based on the movement of particular 'tracer' materials. By comparing technological data with raw material transport patterns elements of Late Neanderthal techno-economic behaviour emerge. Raw materials were transferred over longer distances in both the Levallois and Quina techno-complexes compared to the Discoid techno-complexes, where evidence for similar movements are almost entirely absent. Comparing these patterns of raw material provisioning and transfer against the distribution of key Middle Palaeolithic sites forms the basis of a new model for the territorial organisation of Late Neandertal groups in the Aquitaine Basin to be built.